Mapping Coastline Changes In The Mentawai Islands Using Remote Sensing (Georest, 2022)
The Mentawai Islands are an active deformation zone caused by the movement of the Indo-Australian plate under the Eurasian plate at a speed of 5-6 cm/year. The movement of these plates that occur continuously can be a source of earthquake disasters in the future. However, the information on how much the value of the distance to the coastline changes and the direction of the change has not been well mapped. In this study, a mapping of shoreline changes caused by plate movement along the coast in the Mentawai Islands was carried out using Landsat Imagery. The method used in this research is the Overlay method between Landsat Imagery 2005,2010, and 2020 using ArcGIS software and the Digital Shoreline Analysis System (DSAS) which is used to determine the distance between shoreline changes and the direction of the change. Based on the results of the study, it was found that the coast of the Mentawai Islands showed a change in the coastline with the average distance of change, namely Siberut Island of -2,109 m, Sipora Island at -2,979 m, North Pagai Island at -3,282 m, and South Pagai Island -1,557 m. From the results obtained, the distance of significant shoreline changes that occur in South Pagai Island with the direction of change towards the Northeast.